Effects of the Bath Salt with Ginseng Powder on Human Body - HAGIHARA, Mari; WADA, Naoko; NAGUMO, Hirotaka; SUGAWARA, Mitsuharu; MAEDA, Masaharu; SAITO, Masato; ICHIKAWA, Masaru; HARA, Mariko (The Journal of The Japanese Society of Balneology, Climatology and Physical Medicine, 2008)
Ginseng powder was dissolved in the warm water to develop bath salt that contained Ginseng powder (250mg: 1% Ginseng powder, 500mg: 2% Ginseng powder) and it made comparative study of the effects with the tap warm water for seven healthy adults (male 3, female 4, 20.7±0.8 years old). The Ginseng powder of 250mg and 500mg was made so that the bath salt of 25g may become 1% and 2%. The whole body immersion of 15 minutes was done to all subjects under the condition that 1% or 2% cannot be distinguished without tap water bathing. As a result, the warm water with Ginseng powder increased in the changes of the deep thermometer in front of chest between immersion and after bathing, compared with the tap warm water. But there were not significant change of the surface skin temperature on the arm and the tissue blood flow on thigh skin. Therefore, the warm water with Ginseng powder was suspected that the thermo effects and the retaining warmth were good compared with the tap warm water. It seemed that it was possible to use it safely as bath salt for it did not change of the blood pressure, the heart rate, and abnormality of the skin without the case to whom the skin had temporarily flushed, was not additionally recognized.